Genettic diversity aáeáment of finger millet, Eleusine ccoracana (Gaertn), germplasm through RAPD analysis - Fakrudin, B.=700 1 Kulkarni, R.S.; Shashidhar, H.E.; Hittalmani, S.
(En, Es, Fr)
ilus., 17 ref.
Keywords: ELEUSINE CORACANA; VARIACION GENETICA; POLIMORFISMO; TECNICAS ANALITICAS; ITALIA; MIJO